Development of flipped classroom math learning instruments with advocacy-sociograph - Zainnur Wijayanto; Indah Ayu Rukmana; Betty Kusumaningrum; Elang Amadeus Poort (Universitas Sarjanawiyata Tamansiswa, 2023)
The research project described aims to create a Math learning media with a flipped classroom model on